Coalitions for Change - Wolfensohn, James D. (2017)
World Bank Group President, James Wolfensohn addressed the Board of Governors. In the past year the Bank launched a new initiative—the Comprehensive Development Framework (CDF). The aim was to bring the social and the structural aspects of development together with the macroeconomic and the financial so as to establish a much more balanced and effective approach. The Bank will work with the broad development community—the United Nations, the European Union, bilaterals, regional development banks, civil society, and the private sector—to build genuine partnerships. The CDF is now being piloted in 13 countries. The general experience reviewed that strengthening the organization, human capacity, and the structure of the state, both at central and local levels, is the first priority to reduce poverty. The speaker also called for a coalition for change in the new international development architecture in the face of globalization.